Neutralizing and enhancing antibody responses to five genotypes of dengue virus type 1 (DENV-1) in DENV-1 patients - Atsushi Yamanaka (2018)
© 2017 The Authors. Dengue virus (DENV) has four distinct serotypes, DENV-1-4, with four to six genotypes in each serotype. The World Health Organization recommends tetravalent formulations including one genotype of each serotype as safe and effective dengue vaccines. Here, we investigated the impact of genotype on the neutralizing antibody responses to DENV-1 in humans. Convalescent sera collected from patients with primary infection of DENV-1 were examined for neutralizing antibody against single-round infectious particles of the five DENV-1 genotypes (GI-GV). In both GI- and GIV-infected patients, their neutralizing antibody titres against the five genotypes were similar, differing ≤-fold from the homogenotypic responses. The enhancing activities against the five genotypes were also similar in these sera. Thus, the genotype strains of DENV-1 showed no significant antigenic differences in these patients, suggesting that GI- or GIV-derived vaccine antigens should induce equivalent levels of neutralizing antibodies against all DENV-1 genotypes.